2019
DOI: 10.1177/1477370819887517
|View full text |Cite
|
Sign up to set email alerts
|

The Good, The Bad, and The Street: Does ‘street culture’ affect offender communication and reception in restorative justice?

Abstract: This article examines whether and how ‘street culture’ affects offender communication and reception in restorative justice. Drawing on an archival dataset of police-led restorative justice conferences, we analysed the relationship between street cultural capital and offenders’ ability to communicate during restorative justice. We explored how offenders’ social background, measured by street cultural capital, and/or communication abilities affect third-party perceptions of offender sincerity and their likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In contrast to the findings, however, recent research concluded that letters of apology were significantly effective for both property and low-level offences (Wager et al , 2015). In addition, an imbalance in the verbal skills required for direct communication has been reported within the literature, often due to the culture, ethnicity or socioeconomic background of the individuals (Willis, 2020; Willis and Hoyle, 2019). An indirect approach such as a letter of apology may in fact be preferable for some individuals and should not be dismissed entirely.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In contrast to the findings, however, recent research concluded that letters of apology were significantly effective for both property and low-level offences (Wager et al , 2015). In addition, an imbalance in the verbal skills required for direct communication has been reported within the literature, often due to the culture, ethnicity or socioeconomic background of the individuals (Willis, 2020; Willis and Hoyle, 2019). An indirect approach such as a letter of apology may in fact be preferable for some individuals and should not be dismissed entirely.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The role of pardons in restorative justice remains peripheral because interpersonal forgiveness has been considered a 'gift' that should not be forced on victims in restorative justice (Suzuki & Jenkins, 2022). Restorative justice processes can involve victims, offenders, and community members meeting to discuss the harms caused by offending behaviour (Willis & Hoyle, 2022). Restorative justice is an approach that emphasizes more on conditions necessary to bring about justice and equilibrium for both criminal perpetrators and victims.…”
Section: Development Of Restorative Justice In Indonesiamentioning
confidence: 99%
“…The Crime and Courts Act of 2013 has been the legislation that has brought restorative justice into effect in the United Kingdom. Since April 2014, the courts have had the authority to postpone sentencing to provide victims of adult offenders with the opportunity to participate in a restorative justice practice (Willis & Hoyle, 2022). Restorative justice is also endorsed by a variety of legislations, including The Code of Practice for Victims of Crime 2020, the Code of Practice for Conditional Cautions -Adults, the Code of Practice for Youth Conditional Caution, the Director's Guidance on Adult Conditional Cautioning, the Director's Guidance on Youth Conditional Cautioning, and the Cautioning and Diversion Act (Crown Prosecution Service, 2019).…”
Section: Guidelines Implementation Of Restorative Justice In Indonesi...mentioning
confidence: 99%
“…The concept of the "ideal victim" highlights the importance of considering the victim's experience in restorative processes [10]. Although RJ has been applied in a variety of contexts, concerns about potential power imbalances and discrimination remain [11].…”
Section: Theoretical Framework Of Restorative Justicementioning
confidence: 99%